Оцінка впливу стічних вод ТЕС на природні водні об’єкти - Чобан, А.Ф.; Чобан, С.Я. (Національна академія наук України, 2008)
На примере Ладыжинской ТЭС проведен анализ влияния сточных вод на природные водные объекты. Показано, что наибольший антропопрессинг оказывают теплообменные воды и система гидрозолошлакоудаления. On the example of Ladyzhyn heat electric station the analysis of sewage influense on natural water bodies is carried out. It’s shown the strongest anthropopressing upon water bodies is put by heat exchange waters and hydrosystem of slag isolation.